Pengaruh Model Pembelajaran Inkuiri Terbimbing Terhadap Penguasaan Konsep Dan Kemampuan Berpikir Kritis Fisika Peserta Didik Kelas X SMAN 1 Kuripan Tahun Ajaran 2017/2018 - Suci Yeritia; Wahyudi Wahyudi; Satutik Rahayu (Department of Physics Education, Universitas Mataram, 2017)
This research aimed to examine the effect of guided inquiry learning model toward concept mastery and critical thinking ability of physics of X grade students of SMAN 1 Kuripan in academic year 2017/2018. This research was an experimental research with post test only control group design. The population of this research was X MIA students consicted of 3 classes with the total number of the students was 30 for each class. The sample was chosen using cluster random sampling technique. Technique of collecting data of the mastery concept and critical thinking ability using essay test. Gained data was analyzed using manova test. The result of hypotesis test showed , so it was concluded that there was an effect of guided inquiry learning wodel on the mastery of concept and critical thinking ability of physics of X grade students of SMAN 1 Kuripan in academic year 2017/2018.